Probiotic Properties and Bile Salt Hydrolase Activity of Some Isolated Lactic Acid Bacteria - Ghazala Zarin Afridi, Rahila Bano, Muhammad Ilyas, Abdul Qadeer, Wajeeha Zarin Afridi, Sharqa Baigum, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Lactic acid bacteria (LAB) have been studied for their possible probiotic value, particularly in enhancing intestinal health and prophylaxis of gut infections. Their survival during a stressful gastrointestinal passage and valuable relationship with a host hinge on specific properties, such as tolerance to acid and bile, enzymatic action, and antimicrobial capability. This study assessed the probiotic traits and BSH activity of probiotic bacteria strains isolated from diverse natural sources. Methods: one hundred and four LAB isolates were derived from yogurt, curd, pickles, and infants' guts. Each isolate underwent testing for acid and bile salt tolerance, BSH activity, NaCl resistance, antimicrobial activity, auto-aggregation, and antibiotic susceptibility, along with cell surface hydrophobicity. Identification and characterization were done using standard microbiology methods. Statistical tests for significance were conducted using the chi-square test. Results: Most isolates demonstrated strong acid (85.6%) and bile tolerance (73.1%), suggesting their ability to survive in the gastrointestinal environment. BSH activity was observed in 59.6% of the strains, while 68.3% tolerated high NaCl concentrations. Antimicrobial activity and antibiotic sensitivity were recorded in 77.9% and 83.7% of the isolates. Additionally, more than half of the isolates showed high auto-aggregation (60.6%) and hydrophobicity (55.8%), supporting their potential for intestinal adhesion. Conclusion: Many LAB strains exhibited such probiotic characteristics as resistance to gastrointestinal conditions, pathogen suppression, and benign antibacterial properties. These results emphasize the effectiveness of LAB sourced from local regions in developing probiotic products. Additional studies utilizing living organisms are needed to confirm the claimed benefits to health. Keywords: Lactic acid bacteria, probiotics, bile salt hydrolase, acid tolerance, antimicrobial activity, auto-aggregation, hydrophobicity, antibiotic susceptibility